Monisme Identitas Etnik dan Reliji di Mataram Lombok Nusa Tenggara Barat - Fuadi, Abdulloh (Hanifiya: Jurnal Studi Agama-Agama, 2019)
This paper discusses the discourse about the complexity of ethnic and religious identity monism in Mataram Lombok West Nusa Tenggara; Sasak ethnic is Islam, while Balinese ethnic is Hindu. The question is then does religious conversion also include ethnic conversion? Methodologically, this paper is library research. Several notes related to this discourse are as follows: (1) Increasing conflict escalation occurs during the Reformation era. Identity politics emerge and strengthen. In several conflicts at Mataram, the ethnic and religious identity is thickening. (2) There is a complexity between democracy and diversity. Democracy demands unity, while multiculturalism emphasizes particularity. Balancing them is easy in theory but difficult in practice. (3) It must be distinguished between politics and politicization. In the case of Indonesia, ethnic and religious issues are often politicized by some people to achieve their own group goals. (4) Relying on ethnicity is a natural instinct in self-defense and affirming identity. This is not necessary to be troubled and blamed. (5) These problems are like a Pandora's box, a box full of diseases. It was the reform era that opened the box which had been closed or covered by the New Order. What happened in the Reformation Era is the emergence of various ethnic and religious problems which were not recognized during the New Order era.